PENGARUH PENDAPATAN USAHA, BEBAN OPERASIONAL DAN AKTIVA TETAP TERHADAP LABA BERSIH PADA ALFAMART KUTACANE KABUPATEN ACEH TENGGARA - Abi Anwar; Rila Maufira; Bahrul Ilmi (EKSPOLHUM, 2026)
Profitability reflects the extent to which a company can generate income that exceeds its operational costs, thereby ensuring long-term business continuity. This study aims to determine and analyze the influence of operating revenue, operating expenses, and fixed assets on net profit at Alfamart Kutacane in Southeast Aceh Regency. A quantitative research approach was applied, using a census or saturated sampling technique in which the entire population is taken as the sample. Thus, the sample consisted of 60 observations derived from monthly financial data over a five-year period (2020–2024). Secondary data from the company’s financial reports were processed using descriptive statistics, classical assumption tests, multiple linear regression, and both simultaneous and partial hypothesis testing through SPSS software. The findings show that operating revenue, operating expenses, and fixed assets collectively have a positive and significant effect on net profit. However, when tested partially, operating revenue does not demonstrate a positive or significant effect on net profit. Operating expenses, on the other hand, exhibit a significant partial influence, indicating that cost efficiency remains essential in improving profitability. Fixed assets also show a significant and positive partial effect on net profit, suggesting that asset utilization contributes to improved financial performance. These results highlight that effective management of operational costs and productive asset allocation plays a vital role in increasing net profit at Alfamart Kutacane during the 2020–2024 period